The management system for nuclear installations. (International Atomic Energy Agency, 2009)
This safety guide contains detailed recommendations in relation to nuclear installations, to complement the general recommendations provided in IAEA Safety Standards Series No. GS-G-3.1. This safety guide is applicable throughout the lifetime of a nuclear installation, including site evaluation, design, construction, commissioning, operation and decommissioning.--Publisher's description.
"September 2009"--Title page verso.
Keywords: Nuclear power plants -- Management.; Nuclear power plants -- Safety measures.; elektronické knihy; electronic books